UTILIZATION OF HIGHER EDUCATION FACILITIES: A STUDY AMONG IRULA TRIBE IN ATTAPPADY REGION OF KERALA - Muhammed Ashraf T.M and Anas M.K (International Journal of Research in Social Sciences and Humanities, 2018)
Scheduled tribes in India are generally considered to be ‘Adivasis’ meaning indigenous people or original inhabitants of the country. They belong to different racial stocks and religious back grounds and speak different dialects. Discrimination against women, occupational differentiation, and emphasis on status and hierarchical social ordering that characterize the predominant mainstream culture are generally absent among tribal groups. Higher education is education or learning at a College or University. The Accessibility to higher education for Students from scheduled tribe in Attapady is increasingly opting distant places due to the shortage of higher education facilities in their region. The present paper is analyzing the accessibility of higher education for Irula Tribes in Attappady of Kerala. The information was collected from the student’s opted higher education among Irula Tribes through quantitative methodology. Result of the study indicates that, in Attappady there are various kinds of educational barriers and students seeks good education for their better career. Accessibility and utilization of higher education facilities in Attappady is very pathetic. So all tribes are depending outside of the attappady for higher studies. This study further infers that accessibility to higher education for the tribal students’ needs to be improved.